Feasibility and Outcome of PSMA-PET-Based Dose-Escalated Salvage Radiotherapy Versus Conventional Salvage Radiotherapy for Patients With Recurrent Prostate Cancer - Vogel, Marco M. E.; Dewes, Sabrina; Sage, Eva K.; Devecka, Michal; Eitz, Kerstin A.; Gschwend, Jürgen E.; Eiber, Matthias; Combs, Stephanie E.; Schiller, Kilian (Frontiers in Oncology, 2021)
Introduction: Prostate-specific membrane antigen-positron emission tomography-(PSMA-PET) imaging facilitates dose-escalated salvage radiotherapy (DE-SRT) with simultaneous-integrated boost (SIB) for PET-positive lesions in patients with prostate cancer (PC). Therefore, we aimed to compare toxicity rates of DE-SRT with SIB to conventional SRT (C-SRT) without SIB and to report outcome. Material and Methods: We evaluated 199 patients who were treated with SRT between 06/2014-06/2020. 101 patients received DE-SRT with SIB for PET-positive local recurrence and/or PET-positive lymph nodes. 98 patients were treated with C-SRT to the prostate bed +/- elective pelvic lymphatic pathways without SIB. All patients received PSMA-PET imaging prior to DE-SRT ([68Ga]PSMA-11: 45.5%; [18F]-labelled PSMA: 54.5%). Toxicity rates for early (<6 months) and late (>6 months) gastrointestinal (GI) toxicities rectal bleeding, proctitis, stool incontinence, and genitourinary (GU) toxicities hematuria, cystitis, urine incontinence, urinary obstruction, and erectile dysfunction were assessed. Further, we analyzed the outcome with disease-free survival (DFS) and prostate-specific antigen (PSA) response. Results: The overall toxicity rates for early GI (C-SRT: 2.1%, DE-SRT: 1.0%) and late GI (C-SRT: 1.4%, DE-SRT: 5.3%) toxicities ≥ grade 2 were similar. Early GU (C-SRT: 2.1%, DE-SRT: 3.0%) and late GU (C-SRT: 11.0%, DE-SRT: 14.7%) toxicities ≥ grade 2 were comparable, as well. Early and late toxicity rates did not differ significantly between DE-SRT versus C-SRT in all subcategories (p>0.05). PSA response (PSA ≤0.2 ng/mL) in the overall group of patients with DE-SRT was 75.0% and 86.4% at first and last follow-up, respectively. Conclusion: DE-SRT showed no significantly increased toxicity rates compared to C-SRT and thus is feasible. The outcome of DE-SRT showed good results. Therefore, DE-SRT with a PSMA-PET-based SIB can be considered for the personalized treatment in patients with recurrent PC.